The Noah flood narrative within the context of cyclone Idai in Zimbabwe : an exegetical and hermeneutical study of Genesis 6:5 – 9:17 - Chisango, Andrew (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.